New Insights Into DNA Repair Revealed by NucS Endonucleases From Hyperthermophilic Archaea - Zhang, Likui; Jiang, Donghao; Wu, Mai; Yang, Zhihui; Oger, Philippe M. (Frontiers in Microbiology, 2020)
Hyperthermophilic Archaea (HA) thrive in high temperature environments and their genome is facing severe stability challenge due to the increased DNA damage levels caused by high temperature. Surprisingly, HA display spontaneous mutation frequencies similar to mesophilic microorganisms, thereby indicating that the former must possess more efficient DNA repair systems than the latter to counteract the potentially enhanced mutation rates under the harsher environment. Although a few repair proteins or enzymes from HA have been biochemically and structurally characterized, the molecular mechanisms of DNA repair of HA remain largely unknown. Genomic analyses of HA revealed that they lack MutS/MutL homologues of the mismatch repair (MMR) pathway and the recognition proteins of the nucleotide excision repair (NER) pathway. Endonucleases play an essential role in DNA repair. NucS endonuclease, a novel endonuclease recently identified in some HA and bacteria, has been shown to act on branched, mismatched, and deaminated DNA, suggesting that this endonuclease is a multifunctional enzyme involved in NER, MMR, and deaminated base repair in a non-canonical manner. However, the catalytic mechanism and the physiological function of NucS endonucleases from HA need to be further clarified to determine how they participate in the different DNA repair pathways in cells from HA. In this review, we focus on recent advances in our understanding of the function of NucS endonucleases from HA in NER, MMR, and deaminated DNA repair, and propose directions for future studies of the NucS family of endonucleases.